Resolution improvement filter for sonar returns - DYKA, A. (Archives of Acoustics, 1990)
The concern of this paper is the Single Pulse Resolution Filter – SPRF, which is capable of resolving near-rectangular overlapping pulses. The reason for assuming such pulses is that despite the attractive properties of matched filter pulse compression most operational sonar systems continue to use a finite-length rectangular pulse of constant frequency. The task of the SPRF in such system is to improve the short-range resolution and the target detectability in reverberation. The SPRF here discussed has been synthesized on the basis of the ideal deconvolution filter concept by using the semi-heuristic method of the transformation and the supplementing of input signal spectrum. In order to evaluate the SPRF performance three performance indices have been defined, namely the resolution improvement ratio, the degradation in the output signal-to-noise ratio compared to the maximum which is attainable in the matched filter case, and the processing gain against reverberation. The tradeoffs between the performance indices given in an analytic form have been presented and briefly discussed. The results of tests with the SPRF, both in the laboratory and in sea trials are reported. The first of them proves the resolution capability of the SPRF in the case of two, noise-contaminated overlapping returns. The sea trials were carried out during the FAO sponsored BIOMASS First International Biological EX-periment, (FIBEX 81), programme in Antarctica on board the Polish research vessel “Profesor Siedlecki”. A number of echograms produced originally by the Simrad SK-120 echosounder and after having the received signal envelope filtered with the SPRF were recorded simultaneously. Two samples of such echograms recorded on the Brasilian Shelf in April 1981 which show the favourable impact of the SPRF on the picture quality are presented. Finally, the drawbacks of the SPRF are mentioned.